Document examinations in Malta - Calafato, Trevor (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The forensics of documents in Malta is constantly increasing in demand. This need is a reaction to the control of human trafficking and the international threat of terrorism, amongst other crimes in Malta and Europe. Besides the constant updates in the Criminal Code, document fraud analysts are increasingly in demand to ensure a more thorough and scientific analysis of forgeries of documents, stamps, seals and private writings.
Keywords: Malta; kodeks karny; kryminalistyczna analiza dokumentów; fałszerstwo; podróbka